2017
DOI: 10.3233/nre-172153
|View full text |Cite
|
Sign up to set email alerts
|

Novel multi-pad functional electrical stimulation in stroke patients: A single-blind randomized study

Abstract: The findings suggest that novel FES therapy combined with conventional rehabilitation is more effective on walking speed, mobility of the lower extremity, balance disability and activities of daily living compared to a conventional rehabilitation program only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
0
10
0
4
Order By: Relevance
“…Electrical stimulation has been studied previously for stroke rehabilitation whereby FES was applied during the swing phase of walking to activate nerves that stimulate the lower extremity affected by stroke [12][13][14][15][16]. Many previous studies have observed the positive effect of FES on the gait ability of stroke patients [15,16,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical stimulation has been studied previously for stroke rehabilitation whereby FES was applied during the swing phase of walking to activate nerves that stimulate the lower extremity affected by stroke [12][13][14][15][16]. Many previous studies have observed the positive effect of FES on the gait ability of stroke patients [15,16,26].…”
Section: Discussionmentioning
confidence: 99%
“…Active, ongoing research has demonstrated that neuromuscular electrical stimulation has a positive effect on restoring lower limb motor function and on improving balance and gait [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Ряд исследований свидетельствует о статистически значимом улучшении скорости ходьбы во время проведения 10-минутного теста ходьбы (10 min walking test) как при отдельном использовании аппарата ФЭС, так и в сочетании с традиционной реабилитацией [30][31][32]. Результаты другого исследования показали статистически значимое повышение скорости ходьбы и улучшение последовательности шага после 6 мес применения ФЭС (p < 0,001) [33].…”
Section: сравнительная характеристика эффективности функциональной электростимуляции и голеностопного ортезаunclassified
“…По крайне мере 11 европейских исследований продемонстрировали эффективность применения ФЭС с целью улучшения дорсифлексии и увеличения скорости ходьбы у пациентов, имеющих падающую стопу (foot drop). Еще четыре подобных рандомизированных контролируемых [30,32,34,41] и одно когортное [44] исследование доказывают увеличение скорости ходьбы на фоне применения ФЭС. Так, R. van Swigchem и соавт.…”
Section: влияние функциональной электрической стимуляции на диапазон движений в голеностопном суставе и клиренс стопыunclassified
See 1 more Smart Citation